Listening to Salsa : Gender, Latin Popular Music, and Puerto Rican Cultures - Aparicio, Frances R. (Book collections on Project MUSE., 1998)
"Insightful study of Afro-Caribbean salsa music among Puerto Ricans relates different meanings in salsa lyrics to issues of gender, race, class, and national identities, both in Puerto Rico and Latino communities in the US. Aparicio, a literary critic, uses a postmodern approach to analyze diverse musical texts"--Handbook of Latin American Studies, v. 58.